Dufour and Hall Effects on MHD Flow past an Exponentially Accelerated Vertical Plate with Variable Temperature and Mass Diffusion - A. Selvaraj, S. Constance Angela, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this problem approach, the combined study of the Dufour Effect and Hall Effect on a Magnetohydrodynamic flow past an Exponentially Accelerated Vertical Plate with varying Temperature and Mass Diffusion. An electrically conducting incompressible viscous fluid in a non-scattering medium is considered here. Also, we have applied the basic fundamental of fluid flow equations for the components such as Temperature, Velocity and Concentration was acquired by the Laplace Transforms Technique. The graphical representation for various parameters such as Schmidt Number, the Magnetic Field Parameters, Dufour Number, Time, Prandtl Number and Grashof Number involved in the equations was originated using MATLAB software. It is monitored that there is a drop in the temperature and velocity when the Prandtl number is raised. The graph also validates an increase in temperature when the Schmidt number is increased. After some point (0.5), there is a sudden drop in the temperature.